Immunomodulatory Effects of Dietary β-glucan and Vitamin C in Nile Tilapia, Oreochromis niloticus L., Subjected to Cold-induced Stress or Bacterial Challenge - Barros, Margarida M. [UNESP]; Falcon, Dario R. [UNESP]; Orsi, Ricardo O. [UNESP]; Pezzato, Luiz E. [UNESP]; Fernandes Junior, Ademir C. [UNESP]; Fernandes Junior, Ary [UNESP]; de Carvalho, Pedro L.P.F. [UNESP]; Padovani, Carlos R. [UNESP]; Guimarães, Igo G.; Sartori, Maria M.P. [UNESP] (Wiley, 2015)
To determine the dietary β-glucan and vitamin C levels that would enable the fish to cope with different stress, 252 tilapia (16.86 ± 0.24 g) were distributed in thirty six 250-L aquaria and fed experimental diets for 60 d. Diets were supplemented with β-glucan (0.1, 0.2, 0.4, and 0.8%) and vitamin C (400 and 600 mg/kg diet) and distributed in a factorial design that included a control diet (0 β-glucan/125 mg vitamin C/kg). After growth performance analyses, a group of 108 fish were subjected to cold-induced stress and another to Aeromonas hydrophila infection. Hematological and immunological parameters were determined before and after the stress. Growth performance was not affected. Red blood cells, hematocrit, mean corpuscular volume, total plasma protein, albumin : globulin ratio and leukocytes, lymphocytes, neutrophils, and monocytes were affected (P < 0.05) by stress and/or diets. The control diet resulted in higher post-infection cortisol (P < 0.05). Liver vitamin C was directly proportional to dietary vitamin C (P < 0.05). The production of hydrogen peroxide and nitric oxide was also affected by diets and/or bacterial challenge (P < 0.05). In total, 0.1-0.2% β-glucan and 600 mg/kg vitamin C increased fish resistance to stress and 0.8% β-glucan resulted in reduced immune responses regardless of the vitamin C supplementation level.